PENTINGNYA MENUMBUHKAN KESADARAN ANAK PADA BUDAYA LOKAL - Shomiyatun (STPI Bina Insan Mulia Yogyakarta, 2019)
The problem in this paper is how important it is to raise children's awareness of local culture. The purpose of this paper is how to grow children's awareness of local culture. Culture is also a national identity that should be respected and guarded and preserved so that our culture does not disappear and become a legacy for our children and grandchildren in the future to maintain and enhance positive culture and want to correct, avoid negative culture. This is our shared responsibility, including the younger generation, and we also need encouragement from various parties because cultural resilience is one of the national identities. The way to foster cultural awareness is by instilling an attitude of multiculturalism from an early age, cultural socialization through educational institutions, organizing various cultural performances, loving and maintain their own culture. Introducing culture to children from an early age will teach our children to have direct contact with culture. So that in the future our children will become generations who are proud of their own national culture, love and preserve noble cultural values ​​and can develop attitudes appreciate the diversity of national culture and diversity in religion.